Development and design validation of a novel network meta-analysis presentation tool for multiple outcomes: a qualitative descriptive study. Issue 6 (10th June 2022) - Phillips, Mark R; Sadeghirad, Behnam; Busse, Jason W; Brignardello-Petersen, Romina; Cuello-Garcia, Carlos A; Kenji Nampo, Fernando; Guo, Yu Jia; Bzovsky, Sofia; Bannuru, Raveendhara R; Thabane, Lehana; Bhandari, Mohit; Guyatt, Gordon H
Abstract : Objective: The Grades of Recommendations, Assessment, Development and Evaluation working group recently developed an innovative approach to interpreting results from network meta-analyses (NMA) through minimally and partially contextualised methods; however, the optimal method for presenting results for multiple outcomes using this approach remains uncertain. We; therefore, developed and iteratively modified a presentation method that effectively summarises NMA results of multiple outcomes for clinicians using this new interpretation approach. Design: Qualitative descriptive study. Setting: A steering group of seven individuals with experience in NMA and design validation studies developed two colour-coded presentation formats for evaluation. Through an iterative process, we assessed the validity of both formats to maximise their clarity and ease of interpretation. Participants: 26 participants including 20 clinicians who routinely provide patient care, 3 research staff/research methodologists and 3 residents. Main outcome measures: Two team members used qualitative content analysis to independently analyse transcripts of all interviews. The steering group reviewed the analyses and responded with serial modifications of the presentation format. Results: To ensure that readers could easily discern the benefits and safety of each included treatment across all assessed outcomes, participants primarily focused on simple information presentations, with intuitive organisational decisions and colour coding. Feedback ultimately resulted in two presentation versions, each preferred by a substantial group of participants, and development of a legend to facilitate interpretation. Conclusion: Iterative design validation facilitated the development of two novel formats for presenting minimally or partially contextualised NMA results for multiple outcomes. These presentation approaches appeal to audiences that include clinicians with limited familiarity with NMAs.